Biological control of Streptomyces sp. UT4A49 to suppress tomato bacterial wilt disease and its metabolite profiling - Manigundan Kaari (Elsevier, 2022)
Objectives: Evaluation of Streptomyces isolated from Udhagamandalam, The Nilgiris, Tamilnadu, India for the biocontrol potential against the phytopathogen Ralstonia solanacearum and its metabolite profiling. Methods: Streptomyces strains were screened for plant growth promotion and antagonistic activity against R. solanacearum in in-vitro. The metabolite profiling of strain UT4A49 was studied through gas chromatography coupled with mass spectroscopy (GC–MS) analysis. Further, the identified lead compound 2,4-Di-tert-butylphenol (2,4-DTBP) was analyzed for its mechanism of action through in-silico docking study. The bioorganic fertilizer (BOF) amended potential Streptomyces strain UT4A49 was studied for biocontrol activity against R. solanacearum on tomato seedlings through pot culture experiments. Results: The Streptomyces strain UT4A49 showed the promising production of indole acetic acid (IAA) (76.0 ± 2.0 µg/ml), siderophore, ammonia, amylase, protease, cellulase as well as it solubilized the phosphate in-vitro. The strain UT4A49 showed strong in vitro antagonistic activity against R. solanacearum with the inhibition zone of 19.83 ± 0.44 mm in diameter. The isolated major compound, 2,4-Di-tert-butylphenol was showed strong inhibition against R. solanacearum. In silico docking study revealed that the 2,4-DTBP showed lower binding energy score with all targeted proteins which found better protein–ligand binding stability. In the pot experiment, biocontrol activity of BOF amended Streptomyces strain UT4A49 showed significant biocontrol efficacy was 78.5% against R. solanacearum in tomato seedlings. The strain UT4A49 was identified as Streptomyces sp. based on its morphological and molecular properties. Conclusions: The detailed literature survey revealed that this is the first report on strong bioactive properties of 2,4-DTBP against R. solanacearum. This present study proved that bioorganic fertilizer amended with Streptomyces sp. UT4A49 is a promising biocontrol agent for tomato bacterial disease control.